2020
DOI: 10.1016/j.jaac.2019.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Mood Symptom Trajectories in Adolescents With Bipolar Disorder

Abstract: Objective: The Course and Outcome of Bipolar Youth study found that children and adolescents with bipolar spectrum disorders followed 1 of 4 distinct mood trajectories over 8 years of follow-up, with as many as 25% of participants showing a predominantly euthymic course. We evaluated whether similar patterns of illness course are observed in adolescents with bipolar I and II disorder who participated in a 2-year clinical trial. Method: A total of 144 adolescents with bipolar I or II disorder, identified shortl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Less recognized are the high rates of suicidal ideation (SI) and attempts associated with early-onset BD and subthreshold "high-risk" conditions (Goldstein et al, 2012;Melhem et al, 2019). High levels of SI are associated with a more deteriorative course of illness in youth with BD (Birmaher et al, 2014;Weintraub et al, 2020). The present study examined whether a brief course of family-focused therapy (FFT) is effective in reducing levels of suicidal thinking and behavior in youth at high risk for BD.…”
Section: Introductionmentioning
confidence: 99%
“…Less recognized are the high rates of suicidal ideation (SI) and attempts associated with early-onset BD and subthreshold "high-risk" conditions (Goldstein et al, 2012;Melhem et al, 2019). High levels of SI are associated with a more deteriorative course of illness in youth with BD (Birmaher et al, 2014;Weintraub et al, 2020). The present study examined whether a brief course of family-focused therapy (FFT) is effective in reducing levels of suicidal thinking and behavior in youth at high risk for BD.…”
Section: Introductionmentioning
confidence: 99%
“…Four cohorts were based on reviews of medical records from naturalistically treated patients, with a total of 363 patients and a period of observation between 1.5 and 15 years [ 29 , 30 , 53 , 55 ]. Two cohorts consisted of follow-up of clinical trial samples, for a total of 220 patients and a period of observation of two years [ 56 , 60 ]. One was a large managed care insurance database, which included 8129 patients and a period of observation of 1.4 years [ 52 ], and one was a nationwide population registry in Denmark, which included up to 519 patients over a 10-year period ( Table 1 ) [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a medical record review on a Spanish sample, children with BD had a chronic course with little inter-episodic recovery [ 54 ]. However, in a prospective follow-up of a clinical trial sample, a substantial proportion (25–30%) of youth with bipolar I or II disorder maintained euthymic states over extended periods [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Weintraub et al ( 97 ) divided mood symptom trajectories of adolescent BD patients after FFT into the following four types: Apparent euthymia (initially responded to treatment well and maintained euthymia), accounting for 29.9% of cases; morbid but apparently improved (poor initial treatment effect but later improved and then maintained euthymia), accounting for 11.1%; mild euthymia (improved initially but symptoms reappeared and residual symptoms remained), accounting for 26.4%; and morbid with mild improvement (had severe symptoms initially and presented with mild euthymia after treatment), accounting for 32.6%; participants in these four groups spent, respectively, 77.7, 53.6, 44.1, and 18.6% of the follow-up weeks in euthymia states. Groups 1 and 2 showed fewer severe depression symptoms at baseline than Groups 3 and 4, and Groups 1 and 2 also showed less suicidal ideation, which meant that the prognosis of BD with more severe depression symptoms and suicidal ideation was poorer ( 97 ). Meanwhile, life stage and the level of therapy at baseline also predicted the division whereby patients in Groups 1 and 2 presented with higher life quality scores than patients in Group 4; patients in Group 2 presented with the highest family happiness levels at baseline and higher school happiness than patients in Groups 3 and 4, which indicated that life quality was related to mood symptoms of patients with BD ( 97 ).…”
Section: Psychotherapymentioning
confidence: 99%